2023
DOI: 10.1111/geb.13628
|View full text |Cite
|
Sign up to set email alerts
|

Including imprecisely georeferenced specimens improves accuracy of species distribution models and estimates of niche breadth

Abstract: Aim Museum and herbarium specimen records are frequently used to assess the conservation status of species and their responses to climate change. Typically, occurrences with imprecise geolocality information are discarded because they cannot be matched confidently to environmental conditions and are thus expected to increase uncertainty in downstream analyses. However, using only precisely georeferenced records risks undersampling of the environmental and geographical distributions of species. We present two r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Thus, for some purposes, positionally inaccurate records need not be discarded (as is common practice; Watcharamongkol et al 2018, Gueta and Carmel 2016). This finding is particularly fortuitous because discarding positionally uncertain occurrence data can limit our ability to estimate range sizes and overestimates exposure to climate change (Smith et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for some purposes, positionally inaccurate records need not be discarded (as is common practice; Watcharamongkol et al 2018, Gueta and Carmel 2016). This finding is particularly fortuitous because discarding positionally uncertain occurrence data can limit our ability to estimate range sizes and overestimates exposure to climate change (Smith et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gábor et al (2020) demonstrated that increased sample sizes do not reduce the negative effects of positional uncertainty. Similarly, Smith et al (2023) showed that discarding data with high positional uncertainty limits our ability to determine species' distribution and climatic niche tolerances properly. In particular, they demonstrated that using only accurate data dramatically reduces range size estimates and overestimates exposure to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, each model was first implemented using the specific set of best environmental variables from the R enmsdm package (Smith, 2021). The best models were identified using as a tuning tool the ‘enmsdm’ R package and its evolution ‘enmsdmX’ (Smith et al, 2023), a complement to the dismo package for R (Hijmans et al, 2017) that provides methods for implementing SDMs and ecological niche models through a set of ‘training’ functions that automatically tune and parameterize models based on several popular algorithms (e.g., Maxent, GLMs, GAMs, etc.). The selection among models with different specifications of predictors can be done using some criteria for instance the Akaike Information Criterion (AICc) (Akaike, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…To this aim, each model was first implemented using the specific set of best environmental variables from the R enmsdm package (Smith, 2021). The best models were identified using as a tuning tool the 'enmsdm' R package and its evolution 'enmsdmX' (Smith et al, 2023), a complement to the dismo package for R (Hijmans et al, 2017) that provides methods for implementing SDMs and ecological niche models through a set of…”
Section: Model Settingsmentioning
confidence: 99%
“…was developed using the selected hyper‐parameters, thinned presence data and 10,000 random pseudo‐absence data points described above. The model was specified using the trainMaxnet function, enmSdmX package (Smith et al, 2023). Thresholds for the final model output were determined using the evalThreshold function, enmSdmX package.…”
Section: Methodsmentioning
confidence: 99%